Digital Storytelling Media to Improve Students' Speaking Skills in Elementary School - Novita Nur Cahyanti; Ermawati Zulikhatin Nuroh (Journal of Education Technology, 2023)
The research conducted was based on the development of digital-based learning media, where it was found that the majority of educators paid little attention to the application of media as a learning tool in the digital era. This study aims to analyze the improvement of students speaking skills when combining the application of digital story media. The research method used in this study is a quantitative method with one group pretest-posttest design. The population used in the study were students from grade V elementary school totaling 23 children. The assessment in the research process uses a speaking skill rubric that contains: pronunciation, grammar, vocabulary selection, speaking fluency, and overall content of the story delivered. From the results of the research, there are data results in the form of a significant value (2-Tailed) worth 0, 000 in the One Sample T- Test results. Where the significant value of 0, 000 is smaller than 0.05 so that H0 is rejected and Hα is accepted. Thus, it can be concluded that digital-based story media can improve students' speaking skills. The impact of the research conducted is that digital story media can help improve students' language skills. Thus, digital story media can be a learning innovation in schools and can be developed again according to the needs of students. So that later it can foster students' creative ideas.